Journal of chemical research. - Societe chimique de France; Gesellschaft Deutscher Chemiker; Chemical Society (Great Britain) ([London] The Chemical Society., 1977)
Contains papers abstracted in: Journal of chemical research. Synopses.
GeoRef
Also published on microfiche.
English, French, or German.
Published on behalf of the Founding Sponsors: Gesellschaft Deutscher Chemiker, Societe chimique de France, and The Chemical Society.
Keywords: Chemistry -- Research -- Periodicals; Chemistry -- Periodicals